The muscarinic acetylcholine M2 receptor-induced nitration of p190A by eNOS increases RhoA activity in cardiac myocytes - Lévay, Magdolna; Throm, Lena; Bahrami, Nabil; Wieland, Thomas (Cells, 2023)
p190RhoGAP, which exists in two paralogs, p190RhoGAP-A (p190A) and p190RhoGAP-B (p190B), is a GTPase activating protein (GAP) contributing to the regulation of the cellular activity of RhoGTPases. Recent data showed that M2 muscarinic acetylcholine receptor (M2R) stimulation in neonatal rat cardiac myocytes (NRCM) induces the binding of p190RhoGAP to the long isoform of the regulator of G protein signaling 3 (RGS3L). This complex formation alters the substrate preference of p190RhoGAP from RhoA to Rac1. By analyzing carbachol-stimulated GAP activity, we show herein that p190A, but not p190B, alters its substrate preference in NRCM. Based on data that the RhoGAP activity of p190A in endothelial cells is diminished upon nitration by endothelial nitric oxide synthase (eNOS)-derived peroxynitrite, we studied whether carbachol-induced NO/peroxynitrite formation contributes to the carbachol-induced RhoA activation in NRCM. Interestingly, the carbachol-induced RhoA activation in NRCM was suppressed by the eNOS-preferring inhibitor L-NIO as well as the non-selective NOS inhibitor L-NAME. Using L-NIO, we firstly verified the carbachol-induced NO production concurrent with eNOS activation and, secondly, the carbachol-induced nitration of p190A in NRCM. By co-immunoprecipitation, the carbachol-induced complex formation of eNOS, p190A, RGS3L and caveolin-3 was detected. We thus conclude that the NO production by M2R-induced eNOS activation in caveolae in NRCM is required for the nitration of p190A, leading to the binding to RGS3L and the change in substrate preference from RhoA to Rac1. In line with this interpretation, the disruption of caveolae in NRCM by methyl-β-cyclodextrin suppressed carbachol-induced RhoA activation in NRCM to a similar extent as the inhibition of NO production.